Prostaglandin D2-Mediated DP2 and AKT Signal Regulate the Activation of Androgen Receptors in Human Dermal Papilla Cells - Jeong, Kwan Ho (Int J Mol Sci, 2018)
Prostaglandin D2 (PGD2) and prostaglandin D2 receptor 2 (DP2) is known to be an important factor in androgenetic alopecia (AGA). However, the effect of PGD2 in human dermal papilla cells (hDPCs) is not fully understood. The function of PGD2-induced expression of the androgen receptor (AR), DP2, and AKT (protein kinase B) signal were examined by using real time-PCR (qRT-PCR), western blot analysis, immunocytochemistry (ICC), and siRNA transfection system. PGD2 stimulated AR expression and AKT signaling through DP2. PGD2 stimulated AR related factors (transforming growth factor beta 1 (TGFβ1), Creb, lymphoid enhancer binding factor 1 (LEF1), and insulin-like growth factor 1, (IGF-1)) and AKT signaling (GSK3β and Creb) on the AR expression in hDPCs. However, these factors were down-regulated by DP2 antagonist (TM30089) and AKT inhibitor (LY294002) as well as DP2 knockdown in hDPCs decreased AR expression and AKT signaling. Finally, we confirmed that PGD2 stimulates the expression of AR related target genes, and that AKT and its downstream substrates are involved in AR expression on hDPCs. Taken together, our data suggest that PGD2 promotes AR and AKT signal via DP2 in hDPCs, thus, PGD2 and DP2 signal plays a critical role in AR expression. These findings support the additional explanation for the development of AGA involving PGD2-DP2 in hDPCs.